DEVELOPMENT OF A MATHEMATICS MODULE BASED ON A CONTEXTUAL APPROACH TO ENHANCE NUMERACY LITERACY - Rima Fitriyani; Happy Lumbantobing; Jonner Nainggolan (Education Studies and Teaching Journal (EDUTECH), 2026)
The primary objective of this research is to develop a mathematics module utilizing a contextual approach to enhance the numeracy literacy skills of eighth-grade students at MTs Negeri Kota Jayapura, specifically focusing on relations and functions. Employing the Research and Development (R&D) method with the ADDIE model, the study progressed through analysis, design, development, implementation, and evaluation stages. The findings indicate that the developed module achieved a "very valid" rating (97.2%) and was deemed "very practical" by practitioners (85.2%) as well as students during small groups (87.6%) and field trials (85.6%). In terms of effectiveness, the classical learning mastery of students using the module reached 93%, significantly surpassing the 19% mastery rate of those who did not. Statistical analyses, including paired and independent t-tests, revealed significant differences in numeracy literacy skills (Sig. <0.05). Furthermore, the N-Gain test confirmed that the improvement in the experimental group was high (0.77), whereas the control group remained low (0.23). Conclusively, this module is proven to be feasible, practical, and effective for improving numeracy literacy.